Konsep Filsafat Ilmu Al-Farabi; Kontribusinya terhadap Pengembangan Ilmu Keislaman - Chair, Badrul Munir (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Al-Farabi is an Islamic philosopher who combining the Plato's and Aristotle's thoughts. Al-Farabi attempted to synergize philosophy with religion thought. This article will describes the Al-Farabi's philosophy of science, and the contribution of Al-Farabi's thinking in development of contemporary Islamic thought. This study is qualitative research with a literature study approach and using the hermeneutic method. In ontology field, Al-Farabi views all things as souls, the One or God as the First Soul, the Soul of all souls. Al-Farabi described his theory of emanation into ten intelligences. In that theory, Al-Farabi explained the causal relation between the First Soul and this physical world. In epistemology field, Al-Farabi's view of the soul is able to answer the question of how humans are able to reveal what is hidden in the universe. This study shows that Al-Farabi's description of the ontological status of science, the division of the soul, and the classification of science has made a major contribution to the development of the philosophy of science in later times. Al-Farabi's concept of epistemology in measuring and assessing knowledge have a very strong impact on the development of contemporary Islamic science, especially in developing rational theology with a Theo-anthrophocentric pattern.